AB0323 Weekly subcutaneous abatacept confers comparable onset of treatment response and magnitude of efficacy improvement over 6 months when administered with or without an intravenous abatacept loading dose. (23rd January 2014) - Schiff, M.; Alten, R.; Weinblatt, M.; Nash, P.; Fleischmann, R.; Durez, P.; Kaine, J.; Delaet, I.; Kelly, S.; Maldonado, M.; Patel, S.; Genovese, M.
Abstract : Background: Previous pharmacokinetic data show that, in the absence of intravenous (IV) loading, target therapeutic concentrations are achieved in the majority of patients (pts) by Week 2 of subcutaneous (SC) abatacept treatment. 1 Objectives: To compare clinical and functional responses with SC abatacept administered with or without an IV loading dose, in pts with active RA and inadequate response to MTX. Methods: Pts from the intent-to-treat populations of the ACQUIRE 2 and AMPLE 3 studies randomized to SC abatacept plus MTX were included in this analysis. All pts received fixed-dose SC abatacept 125 mg/week; in ACQUIRE, pts also received an IV loading dose (∼10 mg/kg based on weight range) on Day 1; no IV loading dose was administered in AMPLE. For this post-hoc analysis, assessments included ACR 20 and Health Assessment Questionnaire-Disability Index (HAQ-DI) response (improvement of ≥0.3) over 6 months, with pts who discontinued considered non-responders. Mean changes from baseline over 6 months in Disease Activity Score (DAS)28 (C-reactive protein [CRP]) were assessed in pts with DAS28 >5.1 at baseline (last observation carried forward) to account for differences in baseline disease activity between the two studies. Results: A total of 736 pts from ACQUIRE (IV loading dose) and 318 pts from AMPLE (no IV loading dose) were included. All pts were biologic-naïve at baseline, with mean disease duration of 7.6 and 1.8 years, DAS28 (CRP) 6.2 and 5.5, and HAQ-DI 1.72 and 1.5 in ACQUIRE and AMPLE, respectively. Efficacy was compared at Days 15, 29, 57, 85, 113, 141 and 169. For pts treated with SC abatacept with an IV loading dose, ACR 20 response rates at these time points were 24.6, 44.5, 58.0, 66.6, 69.3, 72.4 and 74.8%, respectively. For pts treated without an IV loading dose, ACR 20 response rates were similar: 27.4, 42.5, 58.5, 60.1, 66.0, 70.1 and 66.0%, respectively. HAQ-DI response rates were also similar: 31.7, 45.1, 53.5, 59.5, 63.2, 64.4 and 68.3%, respectively, with the IV loading dose, and 31.8, 42.8, 54.4, 58.5, 60.1, 61.9 and 61.0%, respectively, without the IV loading dose. For the overall populations, mean (standard deviation [SD]) changes from baseline to Day 169 in DAS28 were –2.57 (1.30) and –2.09 (1.38) in ACQUIRE and AMPLE, respectively. For pts with baseline DAS28 >5.1, mean (SD) changes in DAS28 from baseline to Day 169 were –2.65 (1.29) and –2.49 (1.35) in ACQUIRE and AMPLE, respectively. Conclusions: Time to onset and magnitude of ACR 20 and HAQ-DI responses and DAS28 improvements were generally similar with SC abatacept with or without IV loading in patients with RA and an inadequate response to MTX. The findings from this post-hoc analysis suggest that SC abatacept can be given effectively without an IV abatacept loading dose. References: Murthy B, et al. Ann Rheum Dis 2011;70 (Suppl 3):459; 2. Genovese MC, et al. Arthritis Rheum 2011;63 (10):2854-64; 3. Schiff M, et al. Ann Rheum Dis 2012;71 (Suppl 3):60. Disclosure of Interest: M. Schiff Consultant for: Bristol-Myers Squibb, Abbvie, Speakers bureau: Bristol-Myers Squibb, Abbvie, R. Alten Grant/research support from: BMS, Merck Pharma GmbH, Wyeth Pharmaceuticals, Pfizer, Consultant for: bbott Laboratories, Horizon Pharma, Merck Pharma GmbH, Nitec Pharma GmbH, Novartis Pharmaceuticals Corporation, Roche, Speakers bureau: Abbott Laboratories, BMS, Horizon Pharma, Merck Pharma GmbH, Novartis Pharmaceuticals Corporation, Roche, M. Weinblatt Grant/research support from: Bristol-Myers Squibb, Consultant for: Bristol-Myers Squibb, Abbott, P. Nash Grant/research support from: Bristol-Myers Squibb, Consultant for: Bristol-Myers Squibb, Speakers bureau: Bristol-Myers Squibb, R. Fleischmann Grant/research support from: Abvie, Amgen, Astellas, Astra Zeneca, BMS, Celgene, Dynavax, Genzyme, Janssen, Eli Lilly, Merck, Novartis, Pfizer, Roche, Sanofi Aventis, UCB, Xoma, Consultant for: Abvie, Amgen, Astra Zeneca, BMS, Celgene, Janssen, Eli Lilly, Pfizer, Roche, Sanofi Aventis, UCB, P. Durez Speakers bureau: Bristol-Myers Squibb, J. Kaine Grant/research support from: Bristol-Myers Squibb, Speakers bureau: Bristol-Myers Squibb, UCB, Inc., I. Delaet Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, S. Kelly Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, M. Maldonado Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, S. Patel Shareholder of: Bristol-Myers Squibb, Employee of: Bristol-Myers Squibb, M. Genovese Grant/research support from: Bristol-Myers Squibb, Consultant for: Bristol-Myers Squibb